Electrolysis of Bacterial Biofilm - Bazargani, Abdollah; Azimi, Arsalan; Farhadi, Pouya; Irvani, Seyed Sina Naghibi; Moatari, Psalm (bioRxiv, 2021)
Biofilms are a significant global health problem and are of most important clinical impediments of the century. Biofilms play a crucial role in antimicrobial resistance and chronic infections by acting as reservoir for microorganisms. Therefore greater understanding of biofilm and novel methods to eliminate them are needed. We considered electrolysis as a contrivance to decompose and disperse the Pseudomonas aeruginosa biofilm in microtiter dishes. We showed electrolysis effectively eliminated the Pseudomonas aeruginosa biofilm with the potential to change our approach in tackling biofilms.